Active mass driver system as the first application of active structural control. - Ikeda, Yoshiki (Earthquake engineering & structural dynamics.)
An active mass damper (AMD) system has been installed in a ten storey office building in Tokyo to suppress vibration in both one translational and the torsional directions under earthquake and wind loadings. This installation is the first application of active structural control in the civil engineering field. This paper describes the objective building and its dynamic properties, the composition and specification of the AMD system, the control strategy, the control purpose and the system's effectiveness based on observation records. The control strategy has basically been introduced as an output feedback control law that is simplified from a state feedback control law in the linear quadratic regulator problem. The responses of both the structure and the AMD system have been recorded since 1989. A structure-controller interaction model is identified to simulate the earthquake observation records and to compare them with the analysed uncontrolled responses. An ARX model is fitted to each set of these observation records to evaluate the control effectiveness as equivalent damping ratios in the vibration modes. Both the simulation and the system identification confirm that the AMD system achieves the control purpose under earthquake excitations. The wind observation records also show high control effectiveness.